DIALECTICS OF ISLAMIC LEFT THEOLOGY: HASAN HANAFI’S THOUGHT ON PALESTINIAN OPPRESSION - Firmansyah, Agus; Miko, Setia (International Journal of Multidisciplinary Reseach, 2025)
This study examines Hasan Hanafi’s concept of Islamic Left Theology as a framework for social liberation and resistance against global injustice, particularly the oppression of Palestine by Zionist Israel. Employing a qualitative descriptive method through library research, the paper explores Hanafi’s philosophical and theological paradigm that integrates faith with praxis. Hanafi views Islam as a revolutionary force that must liberate humanity from all forms of domination political, economic, and cultural by reinterpreting classical traditions through at-Turats wa at-Tajdid (Heritage and Renewal). His notion of “Islamic Left” emphasizes rational, ethical, and humanistic values to confront Western hegemony and to reconstruct Muslim consciousness toward justice and equality. The findings reveal that Hanafi’s call for Oksidentalisme (Occidentalism) provides an alternative intellectual strategy for Islamic civilization to critically engage the West while affirming its own identity. This theological approach contributes to understanding Islam not merely as a spiritual system but as a transformative ideology for human liberation and social justice.